2018
DOI: 10.1021/acs.jmedchem.8b01060
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Inhibitors of Mosquito Acetylcholinesterase 1 with Resistance-Breaking Potency

Abstract: Resistance development in insects significantly threatens the important benefits obtained by insecticide usage in vector control of disease-transmitting insects. Discovery of new chemical entities with insecticidal activity is highly desired in order to develop new insecticide candidates. Here, we present the design, synthesis, and biological evaluation of phenoxyacetamide-based inhibitors of the essential enzyme acetylcholinesterase 1 (AChE1). AChE1 is a validated insecticide target to control mosquito vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…For instance, larvicidal inhibitors have the ability to bind to sterol carrier protein-2 [56], juvenile hormone-binding protein [57], D7r4 a salivary biogenic amine-binding protein [58], calcium-dependent protein kinase-1 [59], or purine nucleoside phosphorylase targets [60]. The binding investigation of the dihydroquinazolines against the above-mentioned molecular targets allowed us to identify AChE as the most plausible molecular target which corroborated with the predicted brain cell permeability [51][52][53][54][55][56][57][58][59][60]. No crystal structures of Anopheles arabienesis AChE from mosquito are deposited in the Protein Data Bank (PDB) so far.…”
Section: Molecular Modelingsupporting
confidence: 52%
See 2 more Smart Citations
“…For instance, larvicidal inhibitors have the ability to bind to sterol carrier protein-2 [56], juvenile hormone-binding protein [57], D7r4 a salivary biogenic amine-binding protein [58], calcium-dependent protein kinase-1 [59], or purine nucleoside phosphorylase targets [60]. The binding investigation of the dihydroquinazolines against the above-mentioned molecular targets allowed us to identify AChE as the most plausible molecular target which corroborated with the predicted brain cell permeability [51][52][53][54][55][56][57][58][59][60]. No crystal structures of Anopheles arabienesis AChE from mosquito are deposited in the Protein Data Bank (PDB) so far.…”
Section: Molecular Modelingsupporting
confidence: 52%
“…On the basis of the preliminary structure-activity relationship of the 2,3-dihydroquinazolin-4(1H)-one derivatives, we explored a variety of enzyme molecular targets in an attempt to identify the mode of action via which the compounds exert their larvicidal effect. It is well known that AChE represents the main molecular target of insecticides [51][52][53][54][55] and can be associated with the larvicidal action of our compounds. However, some insecticide enzyme targets other than AChE were reported.…”
Section: Molecular Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…We also investigated the binding pose of the 4‐methyl‐3‐nitrobenzamide scaffold by determining the X‐ray crystal structure of the complex between 1 a and Mus musculus AChE ( m AChE) at a resolution of 2.3 Å (Table S2). h AChE and m AChE are very similar in sequence and 3D structure, and studies have shown similar inhibition kinetics [66,67] . Also, binary OPNA‐AChE complex structures determined in both species are similar [12,13,15,16] .…”
Section: Resultsmentioning
confidence: 75%
“…In addition, PyrimidineTrione Furan-substituted (PTF) compounds have been observed to preferentially bind mutated G119S AChE [223]. Knutsson et al [224] designed, synthesized and evaluated the biological activity of phenoxyacetamide-based inhibitors of AgAChE and observed that these inhibitors were highly selective for AgAChE compared to hAChE. Also, these inhibitors were effective towards AgAChE with G119S mutation.…”
Section: Generation Of Organism-target Specific and Selective Insectimentioning
confidence: 99%